2017
DOI: 10.1002/cctc.201601132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Catalytic Performance and Carbon Monoxide Sensing Behavior of Pd‐SnO2 Core@Shell Nanocomposites

Abstract: The catalytic activity of Pd‐SnO2 core@shell nanocomposites in the oxidation of CO and their CO‐sensing behavior were compared. For this purpose, Pd particles were placed on the inside and the outside of SnO2 hollow spheres, as demonstrated by electron tomography, X‐ray photoelectron spectroscopy, and X‐ray absorption spectroscopy. Both the sensing and catalytic effect were studied in a systematic manner on such nanocomposites, and striking differences in the catalytic performance of the nanocomposites in CO o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Pd‐ or bimetallic Pd‐Pt‐based materials are applied, for example, for the oxidation of CH 4 or unburned hydrocarbons in the exhaust of natural gas vehicles. Furthermore, systems consisting of Pt/Pd‐SnO 2 or Pt/Pd‐CeO 2 are well known for their good catalytic oxidation properties, for example, in low‐temperature CO oxidation …”
Section: Catalysis and Sensing Of Co And Ch4mentioning
confidence: 99%
See 4 more Smart Citations
“…Pd‐ or bimetallic Pd‐Pt‐based materials are applied, for example, for the oxidation of CH 4 or unburned hydrocarbons in the exhaust of natural gas vehicles. Furthermore, systems consisting of Pt/Pd‐SnO 2 or Pt/Pd‐CeO 2 are well known for their good catalytic oxidation properties, for example, in low‐temperature CO oxidation …”
Section: Catalysis and Sensing Of Co And Ch4mentioning
confidence: 99%
“…Similar to CH 4 sensing, the optimal operation temperature for sensing of CO is decreased by the addition of noble metals . Here, recent operando studies revealed that, similar to the improvement of the catalytic activity in CH 4 combustion, not the noble metal but mostly oxidized Pd species led to the improved sensing properties . This leads to a pronounced structure sensitivity reflected by influence of size, morphology, support and gas atmosphere.…”
Section: Catalysis and Sensing Of Co And Ch4mentioning
confidence: 99%
See 3 more Smart Citations